Resistin-Like Molecule α Dysregulates Cardiac Bioenergetics in Neonatal Rat Cardiomyocytes - Tao, Bingdong; Kumar, Santosh; Gomez-Arroyo, Jose; Fan, Chunling; Zhang, Ailan; Skinner, John; Hunter, Elizabeth; Yamaji-Kegan, Kazuyo; Samad, Idris; Hillel, Alexander T.; Lin, Qing; Zhai, Wenqian; et al. (Frontiers in Cardiovascular Medicine, 2021)
Heart (right) failure is the most frequent cause of death in patients with pulmonary arterial hypertension. Although historically, increased right ventricular afterload has been considered the main contributor to right heart failure in such patients, recent evidence has suggested a potential role of load-independent factors. Here, we tested the hypothesis that resistin–like molecule  (RELM), which has been implicated in the pathogenesis of vascular remodeling in pulmonary artery hypertension, also contributes to cardiac metabolic remodeling, leading to heart failure. Recombinant RELM (rRELM) was generated via a Tet-On expression system in the T-REx 293 cell line. Cultured neonatal rat cardiomyocytes were treated with purified rRELMα for 24 h at a dose of 50 nM. Treated cardiomyocytes exhibited decreased mRNA and protein expression of peroxisome proliferator-activated receptor gamma coactivator 1α (PGC-1α) and transcription factors PPARα and ERRα, which regulate mitochondrial fatty acid metabolism, whereas genes that encode for glycolysis-related proteins were significantly upregulated. Cardiomyocytes treated with rRELM also exhibited a decreased basal respiration, maximal respiration, spare respiratory capacity, ATP-linked OCR, and increased glycolysis, as assessed with a microplate-based cellular respirometry apparatus. Transmission electron microscopy revealed abnormal mitochondrial ultrastructure in cardiomyocytes treated with rRELM. Our data indicate that RELM affects cardiac energy metabolism and mitochondrial structure, biogenesis, and function by downregulating the expression of the PGC-1α/PPARα/ERRα axis.